2003
DOI: 10.1046/j.1460-9568.2003.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Mu‐ and delta‐opioid receptor antagonists decrease proliferation and increase neurogenesis in cultures of rat adult hippocampal progenitors

Abstract: Opioids have previously been shown to affect proliferation and differentiation in various neural cell types. In the present study, cultured rat adult hippocampal progenitors (AHPs) were shown to release beta-endorphin. Membrane preparations of AHPs were found to bind [125I]beta-endorphin, and immunoreactivity for mu- and delta-opioid receptors (MORs and DORs), but not for kappa-opioid receptors (KORs), was found on cells in culture. Both DNA content and [3H]thymidine incorporation were reduced after a 48-h inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 57 publications
4
100
0
Order By: Relevance
“…The lack MOR and KOR expression by GRPs at 1 DIV was unexpected. Prior findings indicate that neural and glial precursors can express opioid receptors (Reznikov et al, 1999;Persson et al, 2003a;Persson et al, 2003b;Khurdayan et al, 2004;Kim et al, 2006;Hahn and Knapp, unpublished). The stress of isolating GRPs in culture and/or the loss of key factors available within the extracellular milieu in vivo may temporarily shut down opioid receptor expression.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The lack MOR and KOR expression by GRPs at 1 DIV was unexpected. Prior findings indicate that neural and glial precursors can express opioid receptors (Reznikov et al, 1999;Persson et al, 2003a;Persson et al, 2003b;Khurdayan et al, 2004;Kim et al, 2006;Hahn and Knapp, unpublished). The stress of isolating GRPs in culture and/or the loss of key factors available within the extracellular milieu in vivo may temporarily shut down opioid receptor expression.…”
Section: Discussionmentioning
confidence: 90%
“…The particular effects seen for each receptor type are contextual and differ among cell types and at different stages of development. Immature neurons Eisch and Harburg, 2006;Narita et al, 2006a), astrocytes (Stiene-Martin and Hauser, 1990;Eriksson et al, 1990;Eriksson et al, 1991;Stiene-Martin and Hauser, 1991;Hauser et al, 1996;Stiene-Martin et al, 1998;Belcheva et al, 2005), oligodendrocytes (Knapp et al, 1998;Stiene-Martin et al, 2001), and their precursors (Persson et al, 2003a;Persson et al, 2003b;Persson et al, 2006;Kim et al, 2006) can respond uniquely to opioids. For example, MOR receptor activation can inhibit proliferation in immature astroglia, while activation of the same receptor type in immature oligodendroglia increases proliferation (Knapp et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study supports both the presence of MOR on hippocampal progenitors cells as well as the role of MOR in neuronal fate specification (Persson et al, 2003), and an in vivo study shows the presence of MOR on progenitors in another neurogenic region of the brain, the SVZ (StieneMartin et al, 2001). Furthermore, MOR may be expressed on a small population of cells of unknown identity in the dentate gyrus (Drake and Milner, 1999); these cells deserve further analysis for the possibility that they are progenitor cells.…”
Section: Possible Mechanisms For Mor Regulation Of Neurogenesismentioning
confidence: 84%
“…With respect to inducible proliferation, our data are consistent with a number of recent studies implicating MAPK signaling in progenitor cell proliferation. For example, neuromodulators such as cannabinoids, opioid, NPYas well as the mood stabilizer valproate increase neurogenesis via a MAPK-dependent mechanism (Hao et al, 2004;Howell et al, 2005;Jiang et al, 2005;Persson et al, 2003;Reuda et al, 2002). Furthermore, vascular endothelial growth factor-mediated proliferation of retinal progenitor cells is also dependent on MAPK signaling (Hashimoto et al, 2006), and using a slice culture technique, MAPK signaling has been shown to stimulate hypoxiainduced neurogenesis (Zhou and Miller, 2006;Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%